HUTSULSHCHUNA IN THE СREATIVE WORK OF BOHDAN LEPKYI: LYRIC «I» ON THE BASIC OF THE CARPATHIAN - Vasylchuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The attempt to watch the origin and the history of well-known Ukrainian writer Bohdan Lepkyi (1871–1941) poetic cycle «V Roztokakh» is made in this article. The author tries to understand the sources of reasons, which are the basis of the poetical cycle. The systems of characters are also watched. The investigator tries to find out how much the poet is interested in the theme of Hutsulshchyna. The tries to understand if he could live into the Carpatian problems. The main symbols of the cycle are shown. They are read and work on the level with conceptions. At in also shown the connect on of modernism poetry cycle and poems of social sounding.